How strong are salt marshes? Geotechnical properties of coastal wetland soils. Issue 6 (28th January 2022) - Brooks, Helen; Moeller, Iris; Spencer, Tom; Royse, Katherine; Price, Simon; Kirkham, Matt
Abstract: Salt marshes are globally distributed, vegetated intertidal wetlands and marsh edge erosion is common on many shores. To understand how and why marsh edge erosion occurs, the response of salt marsh substrates to applied shear and vertical stress must first be quantified. This response is likely influenced by marsh substrate biological, geochemical and sedimentological composition. However, currently there is little systematic research into the between‐marsh variability in these properties and how they affect both marsh edge erosion processes and the ability of a marsh to maintain its position vertically within the tidal frame. This paper compares two marshes of contrasting sedimentology at Tillingham marsh, East England and Warton marsh, Northwest England. Soil shear strength and compressibility are determined by applying geotechnical methods to determine marsh resistance to shear and vertical effective stresses. This research was able to isolate the influence of roots on substrate shear strength in a three‐dimensional sample. In response to vertical effective stress, both the expected displacement magnitude and the vertical recovery potential of a marsh substrate are affected by past stress conditions on the marsh, particularly those resulting from desiccation. The substrate response to vertical effective stress also influences substrate shear strength through the effect of consolidation on the void ratio (or bulk density). We present evidence for the connection between marsh composition and substrate behaviour under applied stress. The results shed light on potential determinants of marsh resistance to edge erosion, which is ultimately essential for the informed implementation of both nature‐based coastal flood defences and coastal restoration schemes. Abstract : Geotechnical methods are applied to salt marsh substrates to understand substrate behaviour in response to applied stress. We find that the behaviour of marsh substrates depends on substrate composition. These findings have implications for marsh edge erosion and the ability of a marsh platform to maintain its elevation within the tidal frame, which ultimately affect future landform change.